The second generation of HIV-1 vertically exposed infants: a case series from the Italian Register for paediatric HIV infection. - Calitri, Carmelina; Gabiano, Clara; Galli, Luisa; Chiappini, Elena; Giaquinto, Carlo; Buffolano, Wilma; Genovese, Orazio; Esposito, Susanna; Bernardi, Stefania; de Martino, Maurizio; Tovo, Pier-Angelo (BMC Infect Dis, 2014)
BACKGROUND: In the Highly Active Antiretroviral Therapy (HAART) era, the prognosis of children perinatally infected with HIV-1 has significantly improved, so the number of perinatally-infected females entering child-bearing age and experiencing motherhood is increasing. METHODS: A description of the medical history and pregnancy outcomes of women with perinatal acquired HIV-1 infection enrolled in the Italian Register for HIV infection in Children. RESULTS: Twenty-three women had 29 pregnancies. They had started an antiretroviral therapy at a median of 7.7 years (interquartile range, IQR 2.3 - 11.4), and had experienced a median of 4 therapeutic regimens (IQR 2-6). Twenty women (87%) had taken zidovudine (AZT) before pregnancy, in 14 cases as a starting monotherapy. In 21 pregnancies a protease inhibitor-based regimen was used. At delivery, the median of CD4+ T lymphocytes was 450/μL (IQR 275-522), and no viral load was detectable in 15 cases (reported in 21 pregnancies). Twenty-eight children were delivered through caesarean section (median gestational age: 38 weeks, IQR 36-38, median birth weight: 2550 grams, IQR 2270 - 3000). Intravenous AZT was administered during delivery in 26 cases. All children received oral AZT (median: 42 days, IQR 31 - 42), with no adverse events reported. No child acquired HIV-1 infection. CONCLUSIONS: Despite a long history of maternal infection, multiple antiretroviral regimens and, perhaps, the development of drug-resistant viruses, the risk of mother-to-child transmission does not seem to have increased among the second-generation of HIV-1 exposed infants.
Keywords: Adult; Anti-HIV Agents; Antiretroviral Therapy, Highly Active; Birth Weight; Cesarean Section; Child; Female; HIV Infections; HIV-1; Humans; Infant; Infectious Disease Transmission, Vertical; Italy; Male; Pediatrics; Pregnancy; Pregnancy Complications, Infectious; Pregnancy Outcome; Prospective Studies; Viral Load; Young Adult; Zidovudine

Defective FOXP3 expression in patients with acute Kawasaki disease and restoration by intravenous immunoglobulin therapy. - Olivito, Biagio; Taddio, Andrea; Simonini, Gabriele; Massai, Cristina; Ciullini, Sara; Gambineri, Eleonora; de Martino, Maurizio; Azzari, Chiara; Cimaz, Rolando (Clin Exp Rheumatol, 2010)
OBJECTIVES: The aims of this study were: 1) to investigate forkhead box P3 (FOXP3) expression in patients with Kawasaki disease (KD), exploring possible differences during the acute phase and after defervescence; 2) to evaluate a possible association of the FOXP3 single nucleotide polymorphism (SNP) 543 (SNP ID: rs2232367) with KD. METHODS: FOXP3 expression was evaluated on 8 children with KD and 15 healthy children by flow cytometry and Real-Time polymerase chain reaction (RT-PCR). FOXP3 SNP 543 was genotyped by denaturing high-performance liquid chromatography (DHPLC) and sequencing on DNA samples from 58 additional children with KD and 114 healthy donors. RESULTS: The frequencies of CD4+CD25 +FOXP3+ regulatory T cells were significantly (p=0.0002) lower during the acute phase of KD than in sex- and age-matched healthy donors (median % + SD: 4.8+/-1.3 vs. 7.7+/-1.7) and a similar tendency was revealed for FOXP3 mRNA transcripts (p<0.0001). FOXP3 expression increased significantly, at both protein and mRNA levels, after intravenous immunoglobulin (IVIG) therapy treatment and achieving complete remission of disease (at least 48 hrs; median 9.5 days, range 2-30). Of the 58 patients screened, only one female subject (1.7%) carried the presence of 543 SNP in heterozygosis (C>T; for a total of 1 allele out of 88), with no difference between KD patients and controls (0.0%, 0/203 alleles). CONCLUSIONS: Our data reinforce the notion of an impaired immunoregulation in KD, suggesting also a role of IVIG treatment in modifying the Treg compartment. FOXP3 SNP 543 does not seem to be involved in susceptibility to KD in Italian children.
Keywords: Acute Disease; Child; Child, Preschool; Female; Flow Cytometry; Forkhead Transcription Factors; Genotype; Humans; Immunoglobulins, Intravenous; Infant; Italy; Male; Mucocutaneous Lymph Node Syndrome; Polymorphism, Single Nucleotide; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; T-Lymphocytes, Regulatory